Analisis Faktor Penyebab Keterlambatan Penyediaan Rekam Medis Rawat Jalan di RSUD Dokter Mohamad Saleh Kota Probolinggo - Ulul Azmi; Veronika Vestine; Maya Weka Santi; Gamasiano Alfiansyah (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2025)
The standard time for provided outpatient medical records was ≤ 10 minutes. Based on the results of preliminary study, based on 99 files, 90 medical records (90.9%) experienced delays in provision. The purpose of this study was to analyze the factors caused the delay in provided outpatient medical records at Doctor Mohamad Saleh Hospital, Probolinggo City used the performance theory from Robbins. Type of research used qualitative, data collection techniques were interviews, observations, documentation and brainstorming. The research subjects consisted of 1 head of medical records, 7 outpatient medical record storage officers, 1 medical record distribution officer, 6 outpatient registration officers and 3 nurses. The results of the study were based on ability factors were the lack of knowledge of officers about the procedure for providing outpatient medical records, officers didn’t have medical record education qualifications, officers never participated in medical record management training, and work experience less than 3 years. Based on the opportunity factor were errors in SIMRS, insufficient shelves and storage space for medical records and there was no SOP for provision of outpatient medical records. Meanwhile, the opportunity factor is in the sub-variables of SIMRS, shelves and storage rooms for medical records and SOP. The improvement plan are apply for training, replace officers according qualifications, switch to using RME, improve facilities and infrastructure, and make SOP.